Ulcus vulvae acutum - A rare case - Santoso, Irene Dorthy; Anggraini, Ika; Indriatmi, Wresti; Irawan, Yudo; Nilasari, Hanny; Marissa, Melani; Sirait, Sondang P.; Rihatmadja, Rahadi (UI Scholars Hub, 2019)
Background: Ulcus vulvae acutum, also known as Lipschütz ulcer, is a rare condition characterized by multiple, painful, and acute genital ulceration in young women without venereal infections, associated with systemic symptoms like malaise, fever, and inguinal lymphadenopathy. Case Illustration: A 24-year-old woman developed multiple and painful vulvar ulcers that recurred for almost a year. The patient was primarily diagnosed and treated as genital herpes in several hospitals with only slight improvement and no complete healing. The patient came to our hospital for examinations to rule out sexually-transmitted infection (STI) (genital herpes, syphilis, HIV, and chancroid) and possibility of Behçet’s. The patient was treated with a combination of 2.5% lidocaine and 2.5% prilocaine creams for 1 week, 2% fusidic acid ointment for 1 week, with no significant progression. Later, the therapy was changed to 0.05% clobetasol propionate ointment for 10 days. Complete healing occurred in about 10 weeks with no scarring. Discussion: Diagnosis of ulcus vulvae acutum in this patient was made by excluding other differential diagnoses. Conclusion: Ulcus vulvae acutum is a difficult diagnosis, and clinician should be aware of this entity especially when encountering young woman without previous sexual experience problem with ulcer.